1996
DOI: 10.1126/science.274.5290.1109
|View full text |Cite
|
Sign up to set email alerts
|

Patterning the Vertebrate Neuraxis

Abstract: Neuraxial patterning is a continuous process that extends over a protracted period of development. During gastrulation a crude anteroposterior pattern, detectable by molecular markers, is conferred on the neuroectoderm by signals from the endomesoderm that are largely inseparable from those of neural induction itself. This coarse-grained pattern is subsequently reinforced and refined by diverse, locally acting mechanisms. Segmentation and long-range signaling from organizing centers are prominent among the eme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
607
1
9

Year Published

1999
1999
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 1,071 publications
(627 citation statements)
references
References 89 publications
10
607
1
9
Order By: Relevance
“…The hindbrain region is further partitioned into seven or eight compartments called rhombomeres. Several studies have demonstrated that rhombomeres represent polyclonal compartments (reviewed in Lumsden, 1990) that are distinguished from each other by limited cell movements (Fraser et al, 1990;Birgbauer and Fraser, 1994), differential cell adhesion (Guthrie and Lumsden, 1991;Wizenmann and Lumsden, 1997), differential cell repulsion (Xu et al, 1995(Xu et al, , 1999Cooke et al, 2001;reviewed in Xu et al, 2000;Cooke and Moens, 2002), and compartment-specific expression of homeobox genes (reviewed in Wilkinson and Krumlauf, 1990;Lumsden and Krumlauf, 1996). Each rhombomere contains a characteristic, segmentally reiterated set of neurons, including motor neurons and reticulospinal interneurons (Kimmel et al, 1985;Metcalfe et al, 1986;Lumsden and Keynes, 1989;Clarke and Lumsden, 1993;reviewed in Glover, 2001).…”
Section: The Developing Hindbrainmentioning
confidence: 99%
See 1 more Smart Citation
“…The hindbrain region is further partitioned into seven or eight compartments called rhombomeres. Several studies have demonstrated that rhombomeres represent polyclonal compartments (reviewed in Lumsden, 1990) that are distinguished from each other by limited cell movements (Fraser et al, 1990;Birgbauer and Fraser, 1994), differential cell adhesion (Guthrie and Lumsden, 1991;Wizenmann and Lumsden, 1997), differential cell repulsion (Xu et al, 1995(Xu et al, , 1999Cooke et al, 2001;reviewed in Xu et al, 2000;Cooke and Moens, 2002), and compartment-specific expression of homeobox genes (reviewed in Wilkinson and Krumlauf, 1990;Lumsden and Krumlauf, 1996). Each rhombomere contains a characteristic, segmentally reiterated set of neurons, including motor neurons and reticulospinal interneurons (Kimmel et al, 1985;Metcalfe et al, 1986;Lumsden and Keynes, 1989;Clarke and Lumsden, 1993;reviewed in Glover, 2001).…”
Section: The Developing Hindbrainmentioning
confidence: 99%
“…1), because the array of genetic, genomic, molecular, and embryologic tools available in these organisms holds great promise for elucidating the mechanisms underlying the development of these neurons and their axonal projections. Figure 1 and the following text are based upon data or adapted from figures in the following studies: zebrafish (Kimmel et al, 1985;Hatta et al, 1990;Trevarrow et al, 1990;Chandrasekhar et al, 1997;Schilling and Kimmel, 1997;Higashijima et al, 2000); chick (Lumsden and Keynes, 1989;Simon and Lumsden, 1993;Gilland and Baker, 1993;Simon et al, 1994;Fritzsch, 1996;Lumsden and Krumlauf, 1996;Jacob and Guthrie, 2000); mouse (Carpenter et al, 1993;Gilland and Baker, 1993;Fritzsch, 1996;Studer et al, 1996;SchneiderMaunoury et al, 1997;Garel et al, 2000;Studer, 2001). The neuroanatomy described below is limited to observations up to specific embryonic stages (Fig.…”
Section: Organization Of Bmns and Other Hindbrain Efferent Neuronsmentioning
confidence: 99%
“…The roles of many Hox genes in this process have been determined in mice, where most of the 11 PG1-4 genes have been knocked out singly or in combination (reviewed in Lumsden and Krumlauf, 1996). The classic phenotype associated with Hox loss-of-function mutations in Drosophila is a homeotic transformation to a more anterior segment identity (Lewis, 1978).…”
Section: Hox Gene Function: Specifying Rhombomere Identity and Segmenmentioning
confidence: 99%
“…Following initial regionalization, the anterior hindbrain is partitioned further into a series of morphologically distinct compartments known as rhombomeres (Lumsden and Krumlauf, 1996;Wingate, 2001). Neuronal populations, including cranial motor neurons, arise within specific rhombomeres.…”
Section: Introductionmentioning
confidence: 99%
“…This well-defined patterning of nV motor neuron cell bodies is conserved among mouse, chick, and zebrafish (Chandrasekhar, 2004). Establishment and maintenance of specific rhombomere borders is partially determined by the Hox gene family (Lumsden and Krumlauf, 1996;Moens and Prince, 2002). Along with Hox genes, loss-offunction studies in mouse embryos have demonstrated that Gbx2 also plays a role in the acquisition of AP identity and cell specification in r1-r3.…”
Section: Introductionmentioning
confidence: 99%